Horários de aplicação de herbicidas para o controle de capim amargoso (Digitaria insularis) - Torino, Mateus (2019)
The sourgrass (Digitaria insularis) is a weed that is present in several agricultural crops and causes a significant reduction in productivity. In addition to already presenting resistance to some herbicides. The objective of the present work was to study the control effectiveness of different herbicides, applied at different times, for the control of bitter grass. The experiment was carried out in pots at the experimental farm of the Universidade Tecnológica Federal do Paraná, Câmpus Dois Vizinhos, during the agricultural year of 2018/2019. As experimental units were used plastic pots of 12 kg of soil with 5 plants of bitter grass, kept in the field. The work was carried out with 13 treatments consisted of the herbicides clethodim, clodinafope, fluazifope-p-butyl and haloxyfop, all applied on 11/15/2018, at the hours of 6:00 a.m., 6:00 p.m., 0:00 a.m. and a witness without application. The experimental design was completely randomized (DIC), with four replications. The analyzed variables were phytotoxicity at 7, 14, 21 and 28 days after application (DAA), plant height at 28 DAA and dry mass at 28 DAA. The results showed that all the herbicides caused a certain degree of phytotoxicity on the plants, and the symptoms varied in the first evaluation at 7 DAA of very light for the herbicide Topik, moderate for the herbicides Fusilade and Verdict and very strong for the herbicide Select. In the last evaluation the observed symptoms were of strong for the Topik, very strong for the Fusilade, partial death of the plants for the Verdict and total death of the plants for the herbicide Select. It was concluded that among the tested herbicides, the herbicide Select was the most effective when controlling the weed, when it was applied at 6:00 p.m., followed by the 0:00 a.m. time. The second best was the herbicide Verdict applied regardless of the time.